A Glitch In Photography - Kruyswijk, Anna Elisabeth (Revelar: Revista de Estudos da Fotografia e Imagem, 2016)
When thinking of Photography, the same rectangular shape pops into our minds. Notwithstanding how fixed and  logical this may  seem, 2151   century  Photography has  started   to  show  signals  that   move   away   from  its  conventional   format. The presence of Photography  - in  spatial,  virtual  and  verbal  ways - is being revisited. In many  art practices today, participation  and engagement play a role of increasing importance.  For Photography as a form-bound  practice the interaction with  not only  the eyes but  also the body of the viewer is difficult. Contemporary experimental  photographers  tend  to  somewhat   reject  visual  limitations due  to paper size or screen format,  and  make space for the sudden  and unexpected,  both within   and  outside  the  photographic  system.  With the  two  artists  Katharina Gaenssler (DE, 1974)  and  Rosa Menkman (NL, 1983)  as case-studies, this article will show the integration  of the uncertainty principle in the field of Photography. Here,  manual   craft  and  digital  exploration   cross paths  in  order  to  reach  an updated  body-brain  achievement  for Photography  in agreement  with our current times. Rather than standing still, the viewer is compelled to walk around  in order to grasp  not  only  the  visual  dimension  of  the  photograph  but  also its  level of impact.   The  work  of  the  2151    century   photographer   appeals  to  the  body   as sentimental.